Literature Review: The Relationship between Irregular Sleep Patterns and Cognitive Decline in College Students - Jaizul , Alim; Vera (International Journal of Health, Medicine, and Sports, 2025)
This literature review aims to examine the relationship between irregular sleep patterns and cognitive decline in college students. The method used is a systematic literature review of international scientific articles from 2008-2025 from reputable databases such as PubMed, Scopus, and Web of Science. The results of the study showed that irregular sleep patterns are correlated with decreased academic performance, with an average decrease in GPA of 0.3 points. Students with poor sleep quality (PSQI score >8) showed 15% lower performance on working memory tests. One night of disturbed sleep reduces attention span capacity by 30%. A bidirectional relationship was found between irregular sleep patterns and symptoms of depression and anxiety (OR = 2.1; 95% CI 1.8-2.4), which had a negative impact on cognitive function. Morning light-based interventions increased the Sleep Regularity Index by 15% with an average increase in GPA of 0.2 points, while CBT-I reduced PSQI scores by 5 points and increased working memory by about 12%. Limitations of the study include the dominance of cross-sectional studies from Western countries. It is concluded that regular sleep patterns are a key factor in supporting brain health and academic performance in students. Higher education institutions need to integrate sleep health programs into student services.